2020
DOI: 10.1021/acs.energyfuels.0c01114
|View full text |Cite
|
Sign up to set email alerts
|

Cardanol/SiO2 Nanocomposites for Inhibition of Formation Damage by Asphaltene Precipitation/Deposition in Light Crude Oil Reservoirs. Part I: Novel Nanocomposite Design Based on SiO2–Cardanol Interactions

Abstract: This study aims to design a novel green nanocomposite based on the synergistic effect between silica nanoparticles (SN) and cardanol (CDN). The latter is an environmentally friendly dispersant compound extracted from the cashew nut shell waste. Three cardanol/SiO2 nanocomposites were synthesized and named as 5CSN, 7CSN, and 9CSN based on the mass fraction of cardanol on the surface of the SiO2 nanoparticles of 5, 7, and 9%, respectively. The nanocomposites were characterized by Fourier transform infrared spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 84 publications
0
10
0
Order By: Relevance
“…They concluded that used nanoparticles were effective on suppressing the onset point and reducing the amount of precipitated asphaltenes. López et al investigated the effects of Cardanol/SiO 2 nanocomposites on formation damage by asphaltene precipitation in an asphaltene model solution . They stated that adsorption of n- C 7 asphaltenes onto the surfaces of the Cardanol/SiO 2 nanocomposites decreased the amount of asphaltenes in the bulk solution and lessened the aggregation process.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that used nanoparticles were effective on suppressing the onset point and reducing the amount of precipitated asphaltenes. López et al investigated the effects of Cardanol/SiO 2 nanocomposites on formation damage by asphaltene precipitation in an asphaltene model solution . They stated that adsorption of n- C 7 asphaltenes onto the surfaces of the Cardanol/SiO 2 nanocomposites decreased the amount of asphaltenes in the bulk solution and lessened the aggregation process.…”
Section: Introductionmentioning
confidence: 99%
“…The following section shows the obtained results in terms of the interactions of the SN and CSN nanofluids with the reservoir fluids and rock surface. Considering previous results obtained in the asphaltene adsorption and aggregation tests of n -C 7 asphaltenes in n -heptane/toluene (60/40 volume fraction), in this section, the SN, 5CSN, 7CSN, and 9CSN were evaluated through contact angle and interfacial tension measurements at a nanoparticle concentration of 500 mg·L –1 to determine the nanocomposites with the best behavior in the proposed tests, as detailed in Figure S1. In section , the selected nanoparticles were evaluated at 100 and 300 mg·L –1 to determine the effect of the nanoparticle dosage in the modification wettability and IFT .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Therefore, the main objective of this study is to investigate the applicability of CSN in the asphaltene formation damage inhibition at reservoir conditions based on the IFT, contact angle, imbibition, and coreflooding tests. The study is divided into two parts, Part I: nanocomposite design through SiO 2 –cardanol interactions and Part II: Nanocomposite evaluation and coreflooding test. In the first part, three green nanocomposites of cardanol/SiO 2 were obtained via the anchoring of the cardanol molecules in the nanoparticle surface through the incipient wetness method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the recent developments in nanoscience, nanotechnology has exhibited potential applications in different sections of the petroleum industry, such as exploration and production, drilling operations, enhanced oil recovery (EOR), and petrochemical refinery processes. The potential of nanostructured materials is attributed to their unique properties, such as a large specific surface area, high mechanical and thermal stability, biocompatibility, or electroactivity. These tempting properties make some of them attractive as green chemicals for many situations. Nanoparticles and nanofluids have gained great attention as an efficient alternative solution to traditional techniques for the mitigation of issues induced by asphaltene and wax precipitation and deposition. , …”
Section: Introductionmentioning
confidence: 99%